Estudio de servicios y actividades turísticas para el desarrollo ecoturístico sostenible de la represa Tahuín, cantón Arenillas. - Moncada Cañar, Marlon Ivan; Romero Armijos, Daniela Carolina (Machala : Universidad Técnica de Machala, 2024)
"Study of Tourist Services and Activities for the Sustainable Ecotourism Development of the Tahuín Dam, Cantón Arenillas" focuses on analyzing the ecotourism potential of the Tahuín dam and its surroundings. This involves identifying and evaluating tourism services and activities that could be implemented to promote sustainable development in the area. The methodology used is mixed methodology, combining quantitative and qualitative approaches. A sampling was carried out with the participation of 164 people, including tourists, the local community, representatives of the municipal (GAD) of Arenillas, the Prefecture of El Oro and tourism supply providers. The results of the survey study indicated the viability and interest of tourists in the implementation of innovative and attractive tourist activities such as Flyboard and Bungee Trampoline. These activities not only increase the tourist offer of the dam, but also attract a broader and more diverse audience, and in turn generate the economy for the local community. In this study, the axes of economic, social, environmental and tourist development were analyzed.
"Estudio de Servicios y Actividades Turísticas para el Desarrollo Ecoturístico Sostenible de la Represa Tahuín, Cantón Arenillas" se centra en analizar el potencial ecoturístico de la represa Tahuín y su entorno. Esto implica identificar y evaluar los servicios y actividades turísticas que podrían implementarse para promover un desarrollo sostenible en la zona. La metodología utilizada es metodología mixta, combinando enfoques cuantitativos y cualitativos. Se llevó a cabo un muestreo con la participación de 164 personas, entre las cuales se incluyen turistas, la comunidad local, representantes del (GAD) municipal de Arenillas, la Prefectura de El Oro y proveedores de oferta turística. Los resultados del estudio de las encuetas indicaron la viabilidad y el interés de turistas en la implementación de actividades turísticas innovadoras y atractivas como el Flyboard y el Bungee Trampolín. Estas actividades no solo aumentan la oferta turística de la represa, sino que también atraen a un público más amplio y diverso, y a su vez genera la economía a la comunidad local. En este estudio se analizaron los ejes de desarrollo tanto económico, social, ambiental, turístico.
Keywords: SERVICIOS TURISTICOS; ACTIVIDADES TURISTICAS; FLYBOARD; BUNGEE TRAMPOLIN